Influence of Ergonomics on Traffic Safety and Economy Development - Perić, Teodor; Štrumberger, Nada; Perić, Dean (Promet - Traffic&Transportation, 2004)
As an interdisciplinary science, ergonomics needs to makethe operating of traffic safer, faster and more reliable, for thesake of higher profitability and generally improved economiceffects. This is achieved by adapting and shaping the workplace,machines, transport means, equipment, physical environment,working process etc. according to experience abouthuman anatomic physica~ sociologica~ intellectual and otherminimal, average or maximal capabilities. Therefore, it is necessaryto analyse ergonomics from the standpoint of better productivenessof humans, greater safety (comfort) and security ingeneral.